Music listening in families and peer groups: benefits for young people's social cohesion and emotional well-being across four cultures - Boer, Diana; Abubakar, Amina (Frontiers in Psychology, 2014)
Families are central to the social and emotional development of youth, and most families engage in musical activities together, such as listening to music or talking about their favorite songs. However, empirical evidence of the positive effects of musical family rituals on social cohesion and emotional well-being is scarce. Furthermore, the role of culture in the shaping of musical family rituals and their psychological benefits has been neglected entirely. This paper investigates musical rituals in families and in peer groups (as an important secondary socialization context) in two traditional/collectivistic and two secular/individualistic cultures, and across two developmental stages (adolescence vs. young adulthood). Based on cross-sectional data from 760 young people in Kenya, the Philippines, New Zealand and Germany, our study revealed that across cultures music listening in families and in peer groups contributes to family and peer cohesion respectively. Furthermore, the direct contribution of music in peer groups on well-being appears across cultural contexts, whereas musical family rituals affect emotional well-being in more traditional/collectivistic contexts. Developmental analyses show that musical family rituals are consistently and strongly related to family cohesion across developmental stages, whereas musical rituals in peer groups appear more dependent on the developmental stage (in interaction with culture). Contributing to developmental as well as cross-cultural psychology, this research elucidated musical rituals and their positive effects on the emotional and social development of young people across cultures. The implications for future research and family interventions are discussed.